(untitled) (Research, Society and Development, 2024)
The objective of the article is to expose the history of the composition of the Central Nervous System (CNS) from the perspective of psychopathology and anatomy, revisit the literature on the group of neurotransmitters with small, fast-acting molecules. The other group is composed of neuropeptides, which are larger and slower molecules. Describe the composition of synapses and the importance of neurotransmitters and their classes, and also explain the psychopathology associated with psychosocial factors and neurotransmitters. This is a bibliographical research based on a literature review, narrative type. It is the neuropsychological functions of the brain that have the power to process experiences, transforming them into knowledge. The Central nervous system is a kind of substrate that supports the psychic and expands the neural network. There are more than 50 chemical substances that act as synaptic transmitters, they are the integrative functions of the nervous system that channel information considered important to the integrative regions. The emotions felt by each person are a response to a certain chemical release in the body, but this goes further and involves the psychosocial environment of each individual. In the end, it will be possible to associate which neurotransmitter dysfunctions are related to the main psychopathological disorders, and conclude that the professional in psychology must understand psychopathology, the source of pathological support for the human psyche and the influence of neurotransmitters and the disorders resulting from their imbalance, being Such knowledge is extremely necessary to compose the psychopathological assessment of the demanding patient.